Light-cured mussel bionic acylhydrazone as well as preparation method and application thereof
The preparation of photocured mussel bionic acid hydrazone by Schiff base reaction of vanillin methyl methacrylate and protocatecha benzoylhydrazide, which solved the problems of insufficient adhesion performance and high production cost of existing photocuring adhesives, and achieved the Efficient bonding performance and reduced production costs.
Patent Information
- Application Number
- CN202411532604.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The existing photocuring adhesives have problems such as insufficient adhesion performance and failure to cause shedding, and dopamine raw materials are expensive and chemically active, which increases the difficulty of synthesis and production costs.
Photocured mussel bionic acid hydrazone is prepared by Schiff base reaction through vanillin methyl methacrylate and protocatecha benzoylhydrazide. The synthesis process does not require protection and deprotection of the catechol structure, which simplifies the synthesis steps and Reduced costs.
The combination of catechol structure that simulates mussel adhesion and carbon-carbon double bonds that can participate in photocuring is realized, which improves the adhesion performance of photocuring adhesives, solves the problem of insufficient adhesion ability and failure, and causes shedding. Reduced production costs.
Smart Images

Figure CN119390606A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocurable materials, and in particular relates to photocurable mussel biomimetic acylhydrazone and a preparation method and application thereof. Background Art
[0002] Mussels in the ocean can firmly adhere to the surfaces of various substrates such as metal, glass, polymers and minerals by secreting adhesive protein mucus with fast solidification and super strong waterproof adhesion. Studies have found that this is because there are a large amount of 3,4-dihydroxyphenylalanine (3,4-Dihydroxyphenylalanine, DOPA, also known as dopa) and dopamine (Dopamine, DA) in the adhesive protein. Both dopa and dopamine contain catechol structures, which can adhere to the substrate well. At present, light-curing adhesives generally have insufficient adhesion properties and sometimes fail to fall off. Therefore, mussel bionic materials that may be able to solve the above problems have become a research hotspot.
[0003] However, mussel biomimetic materials in the prior art generally use dopamine as a raw material for chemical modification. On the one hand, dopamine is expensive, which limits the development and application of mussel biomimetic materials. On the other hand, the chemical properties of the catechol structure are active and are easily oxidized into quinone substances under heating or alkaline conditions. Therefore, mussel biomimetic materials need to be protected and deprotected for the catechol structure, which increases the difficulty of synthesis and production costs. Therefore, it is of research significance to find mussel biomimetic materials with a catechol structure that have stable chemical properties, cheap raw materials, and do not require chemical protection for synthesis. Summary of the invention
[0004] The first object of the present invention is to provide a photocurable mussel biomimetic acylhydrazone to solve at least one of the above problems.
[0005] The second object of the present invention is to provide a method for preparing a photocurable mussel biomimetic acylhydrazone to solve at least one of the above problems.
[0006] The third object of the present invention is to provide an application of a photocurable mussel biomimetic acylhydrazone in a mussel biomimetic photocurable adhesive composition to solve at least one of the above problems.
[0007] The fourth object of the present invention is to provide a mussel biomimetic light-curing adhesive composition to solve at least one of the above problems.
[0008] A fifth object of the present invention is to provide a method for preparing a mussel biomimetic photocurable adhesive composition to solve at least one of the above problems.
[0009] In a first aspect, the present invention provides a photocurable mussel biomimetic acylhydrazone, wherein the photocurable mussel biomimetic acylhydrazone has a structural formula as shown in formula (I):
[0010]
[0011] The above-mentioned light-cured mussel biomimetic acylhydrazone is prepared by using vanillin methyl methacrylate and protocatechuic acid benzoyl hydrazide through Schiff base reaction.
[0012] The light-cured mussel biomimetic acylhydrazone of the present invention has a molecular structure that has both a catechol structure that simulates mussel protein and a carbon-carbon double bond that can participate in curing, and is a new type of mussel biomimetic material.
[0013] In a second aspect, the present invention provides a method for preparing a photocurable mussel biomimetic acylhydrazone, the preparation method comprising the following steps:
[0014] Dissolve vanillin methyl methacrylate and protocatechuic benzoyl hydrazide in an organic solvent, add acetic acid in a nitrogen atmosphere, react at 50-80° C. for 1-4 hours, then purify and dry to obtain the product.
[0015] According to the preparation method of the photocurable mussel bionic acylhydrazone of the present invention, vanillin methyl methacrylate and protocatechuic benzohydrazide are subjected to Schiff base reaction to synthesize photocurable mussel bionic acylhydrazone (MH-VM), and the synthesis process does not require protection and deprotection of the catechol structure, the preparation method is simple, and the synthesis difficulty and production cost of the mussel bionic material are reduced.
[0016] In some embodiments, the molar ratio of vanillin methyl methacrylate to protocatechuic acid benzoyl hydrazide may be 1:(0.9-1.3).
[0017] In some embodiments, the organic solvent is selected from at least one of methanol and anhydrous ethanol.
[0018] In some embodiments, the amount of acetic acid used can be 2-5% of the total mass of the reaction system (ie, the total mass of vanillin methyl methacrylate, protocatechuic acid benzoyl hydrazide and acetic acid).
[0019] In some embodiments, the purification treatment method may be to cool to room temperature, filter and wash the solid with an organic solvent until it becomes neutral. Specifically, the organic solvent is selected from at least one of methanol and anhydrous ethanol.
[0020] In other embodiments, the purification treatment method can be cooling to room temperature, filtering, and then washing the solid with anhydrous ethanol precooled at 5° C. to neutralize. Using precooled anhydrous ethanol to wash the solid can increase the yield of the product.
[0021] In some embodiments, the drying treatment method may be to dry the purified solid in a vacuum atmosphere at 25 to 45° C. for 20 to 48 hours.
[0022] In some embodiments, the method for preparing vanillin methyl methacrylate comprises the following steps:
[0023] Mix vanillin, methacrylic anhydride and 4-dimethylaminopyridine, react at 50-80° C. for 24-48 hours in a nitrogen atmosphere, and then purify and dry to obtain the product.
[0024] In some embodiments, the molar ratio of vanillin to methacrylic anhydride may be 1:(1.1-2.0).
[0025] In some embodiments, the amount of 4-dimethylaminopyridine used is 0.2-1% of the total mass of the reaction system (ie, the total mass of vanillin, methacrylic anhydride and 4-dimethylaminopyridine).
[0026] In some embodiments, the purification treatment method can be to first cool to room temperature, add a diluent to the reaction system, first wash with a saturated NaHCO3 solution, then wash with a 0.5 mol / L NaOH solution and a 1 mol / L NaOH solution for 2 to 5 times respectively, and finally wash with deionized water for 2 to 5 times.
[0027] In other embodiments, the diluent may be selected from at least one of dichloromethane and chloroform.
[0028] In other embodiments, the amount of the diluent used may be 50-90% of the total mass of the reaction system (ie, the total mass of vanillin, methacrylic anhydride and 4-dimethylaminopyridine).
[0029] In other embodiments, the volume of the saturated NaHCO3 solution, the 0.5 mol / L NaOH solution, and the 1 mol / L NaOH solution may be 150 to 300 mL.
[0030] In some embodiments, the drying treatment method may be to first collect the purified organic phase, dry it with anhydrous magnesium sulfate, concentrate it, and then dry it in a vacuum atmosphere at 25 to 45° C. for 12 to 36 hours.
[0031] In some embodiments, the preparation method of protocatechu benzoyl hydrazide comprises the following steps:
[0032] Dissolve methyl 3,4-dihydroxybenzoate in an organic solvent, add hydrazine hydrate solution in a nitrogen atmosphere, react at 25-80° C. for 2-24 hours, then purify and dry to obtain the product.
[0033] In some embodiments, the organic solvent is selected from at least one of methanol and anhydrous ethanol.
[0034] In some embodiments, the molar ratio of methyl 3,4-dihydroxybenzoate to hydrazine hydrate is 1:(1.0-2).
[0035] In some embodiments, the mass fraction of hydrazine hydrate in the hydrazine hydrate solution may be 70 to 90%.
[0036] In some embodiments, the purification treatment method may be cooling to room temperature, filtering, and washing the solid with an organic solvent until it becomes neutral. Specifically, the organic solvent is selected from at least one of methanol and anhydrous ethanol.
[0037] In some embodiments, the drying treatment method may be to dry the purified solid in a vacuum atmosphere at 25 to 40° C. for 24 to 48 hours.
[0038] In a third aspect, the present invention provides application of photocurable mussel biomimetic acylhydrazone in a mussel biomimetic photocurable adhesive composition.
[0039] Specifically, the photocurable mussel biomimetic acylhydrazone of the present invention has both the catechol structure, the main chemical structure of mussel adhesion, and a carbon-carbon double bond that can undergo photopolymerization reaction with a resin matrix, and can be used to prepare a photocurable adhesive composition to solve the problem of insufficient bonding ability of photocurable adhesives and shedding due to failure.
[0040] In a fourth aspect, the present invention provides a mussel biomimetic photocurable adhesive composition, which is prepared from a reaction system of a resin matrix, a solvent, a photoinitiator and the above-mentioned photocurable mussel biomimetic acylhydrazone;
[0041] Among them, the mass of the resin matrix can be 50% to 80% of the total mass of the reaction system, the mass of the solvent can be 10% to 20% of the total mass of the reaction system, the mass of the photoinitiator can be 4% to 6% of the total mass of the reaction system, and the mass of the photocured mussel biomimetic acylhydrazone can be 1% to 30% of the total mass of the reaction system.
[0042] In some embodiments, the resin matrix may be polyethylene glycol dimethacrylate, and the number average molecular weight of the polyethylene glycol dimethacrylate is 360-1000.
[0043] In some embodiments, the solvent may be selected from at least one of dimethyl sulfoxide, tetrahydrofuran, and N,N-dimethylformamide.
[0044] In some embodiments, the photoinitiator can be a free radical photoinitiator.
[0045] In other embodiments, the photoinitiator may be selected from at least one of PI-1173, PI-2959, and TPO.
[0046] In some embodiments, the mussel biomimetic light-curable adhesive composition may be cured by placing the mussel biomimetic light-curable adhesive composition under ultraviolet light with a wavelength of 365 to 405 nm for ultraviolet light curing for 60 to 600 seconds.
[0047] In a fifth aspect, the present invention provides a method for preparing a mussel biomimetic photocurable adhesive composition, which comprises dissolving a photocurable mussel biomimetic acylhydrazone in a solvent, adding a resin matrix and a photoinitiator, and mixing them uniformly to obtain the composition.
[0048] The beneficial effects of the present invention are:
[0049] (1) The photocurable mussel biomimetic acylhydrazone of the present invention has low raw material cost; its molecular structure has both a catechol structure that simulates mussel adhesion and a carbon-carbon double bond that can participate in photocuring, and can be used as a new type of mussel biomimetic material;
[0050] (2) The preparation method of the photocurable mussel biomimetic acylhydrazone of the present invention does not require protection and deprotection of the catechol structure during the synthesis process, and the preparation method is simple, which reduces the synthesis difficulty and production cost of the mussel biomimetic material;
[0051] (3) The mussel bionic photocurable adhesive composition prepared by using the photocurable mussel bionic acylhydrazone as a raw material has good adhesive properties and can improve the problem of insufficient adhesion and failure of the photocurable adhesive leading to shedding. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 The synthetic route of the photocurable mussel biomimetic acylhydrazone of the present invention is as follows;
[0053] Figure 2 : is the infrared spectra of VA and VA-MA of Example 3 of the present invention;
[0054] Figure 3 is the hydrogen nuclear magnetic resonance spectrum of VA and VA-MA of Example 3 of the present invention;
[0055] Figure 4 : is the infrared spectra of MD and MD-HH of Example 3 of the present invention;
[0056] Figure 5 MD and MD-HH of Example 3 of the present invention are H NMR spectra;
[0057] Figure 6 This is a comparison diagram of infrared spectra of VA-MA, MD-HH and MH-VM of Example 3 of the present invention;
[0058] Figure 7 is the hydrogen nuclear magnetic resonance spectrum of MH-VM of Example 3 of the present invention;
[0059] Figure 8 The differential scanning calorimetry test results of the mussel biomimetic photocurable adhesive compositions of Examples 4 to 6 of the present invention and the photocurable adhesive composition of Comparative Example 1;
[0060] Fig. 9 This is a schematic diagram of sample preparation for the adhesion performance test of Experimental Example 2 of the present invention;
[0061] Fig.10 The test results of the adhesive properties of the mussel biomimetic photocurable adhesive compositions of Examples 4-6 of the present invention and the photocurable adhesive composition of Comparative Example 1;
[0062] Fig.11 (a) is a TGA curve of the cured films of the mussel biomimetic photocurable adhesive compositions of Examples 4 to 6 of the present invention and the photocurable adhesive composition of Comparative Example 1, Fig.11 (b) is a DTG curve of the cured films of the mussel biomimetic photocurable adhesive compositions of Examples 4-6 of the present invention and the photocurable adhesive composition of Comparative Example 1;
[0063] Fig.12 (a) is an infrared absorption peak diagram of the main functional groups of the mussel biomimetic photocurable adhesive composition of Examples 4 to 6 of the present invention and the photocurable adhesive composition of Comparative Example 1 before curing, Fig.12 (b) is the infrared absorption peak diagram of the main functional groups of the mussel biomimetic photocurable adhesive compositions of Examples 4 to 6 of the present invention and the photocurable adhesive composition of Comparative Example 1 after curing. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with the embodiments. The examples are only for explanation and are not intended to limit the present invention in any way. Unless otherwise specified, the raw materials and reagents used in the examples are conventional products that can be obtained commercially; the experimental methods in the examples where specific conditions are not specified are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer.
[0065] The synthesis route of the photocurable mussel biomimetic acylhydrazone (MH-VM) of Examples 1-3 of the present invention is as follows: Figure 1 shown.
[0066] Example 1
[0067] This embodiment provides a method for preparing a photocurable mussel biomimetic acylhydrazone, comprising the following steps:
[0068] 30 g of vanillin (0.20 mol), 45 g of methacrylic anhydride (0.29 mol) and 0.6 g of 4-dimethylaminopyridine were added to a 250 mL three-necked flask equipped with a mechanical stirring device and a condenser. After nitrogen was introduced into the three-necked flask to expel oxygen, the mixture was stirred for 48 h under a nitrogen atmosphere and a temperature of 80 ° C., and then cooled to room temperature. After adding 150 mL of dichloromethane, the mixture was transferred to a separatory funnel, first washed with 300 mL of saturated NaHCO3 solution until no bubbles were generated in the mixture, and then washed with 300 mL of 0.5 mol / L NaOH solution and 300 mL of 1 mol / L NaOH solution for 3 times, respectively, and finally washed with deionized water for 3 times, the organic phase was collected and dried with anhydrous magnesium sulfate overnight, the organic phase was concentrated with a rotary evaporator, and the concentrated organic phase was transferred to a glass culture dish, and the glass culture dish was placed in a vacuum oven at 25 ° C. and vacuum dried for 36 h to obtain a first intermediate product as a white solid;
[0069] 16.8 g of methyl 3,4-dihydroxybenzoate (0.10 mol) and 200 mL of anhydrous ethanol were added to a 250 mL three-necked flask equipped with a mechanical stirring device and a condenser, and the mixture was stirred for 15 minutes until methyl 3,4-dihydroxybenzoate was dissolved in anhydrous ethanol. Nitrogen was introduced into the three-necked flask to expel oxygen, and 11.01 g of a hydrazine hydrate solution (0.18 mol) with a mass fraction of 80% was added. The mixture was heated to 50° C. and reacted for 18 h, then cooled to room temperature and filtered, and the solid was washed with anhydrous ethanol until it was neutral. The solid was then placed in a vacuum oven and vacuum dried at 25° C. for 36 h to obtain a second intermediate product in the form of a white powder;
[0070] Into a 250mL three-necked flask equipped with a mechanical stirring device and a condenser, 3.5g of the first intermediate product (0.016mol), 3g of the second intermediate product (0.018mol) and 20mL of anhydrous ethanol were added. After nitrogen was introduced into the three-necked flask to expel oxygen, 0.1950g of acetic acid was added dropwise. The mixture was reacted for 3.5h under a nitrogen atmosphere and a temperature of 65°C. The mixture was then cooled to room temperature. The solid was filtered and washed with anhydrous ethanol. The solid was then placed in a vacuum oven and dried in vacuo at 35°C for 48h to obtain a white powder product.
[0071] Example 2
[0072] This embodiment provides a method for preparing a photocurable mussel biomimetic acylhydrazone, comprising the following steps:
[0073] 30 g of vanillin (0.20 mol), 61 g of methacrylic anhydride (0.40 mol) and 0.9 g of 4-dimethylaminopyridine were added to a 250 mL three-necked flask equipped with a mechanical stirring device. After nitrogen was introduced into the three-necked flask to expel oxygen, the mixture was stirred for 24 h under a nitrogen atmosphere and a temperature of 60 ° C., and then cooled to room temperature. After adding 150 mL of dichloromethane, the mixture was transferred to a separatory funnel, first washed with 500 mL of saturated NaHCO3 solution until no bubbles were generated in the mixture, and then washed with 500 mL of 0.5 mol / L NaOH solution and 500 mL of 1 mol / L NaOH solution for 3 times, respectively, and finally washed with deionized water for 3 times, the organic phase was collected and dried with anhydrous magnesium sulfate overnight, the organic phase was concentrated with a rotary evaporator, and the concentrated organic phase was transferred to a glass culture dish, and the glass culture dish was placed in a vacuum oven at 40 ° C. and vacuum dried for 12 h to obtain a first intermediate product as a white solid;
[0074] 16.8 g of methyl 3,4-dihydroxybenzoate (0.1 mol) and 200 mL of anhydrous ethanol were added to a 250 mL three-necked flask equipped with a mechanical stirring device and a condenser, and the mixture was stirred for 15 minutes until methyl 3,4-dihydroxybenzoate was dissolved in the anhydrous ethanol. Nitrogen was introduced into the three-necked flask to expel oxygen, and then 6.88 g of a hydrazine hydrate solution (0.1 mol) with a mass fraction of 80% was added. The mixture was heated to 80° C. and reacted for 2 h, then cooled to room temperature and filtered, and the solid was washed with anhydrous ethanol until it was neutral. The solid was then placed in a vacuum oven and vacuum dried at 35° C. for 24 h to obtain a second intermediate product in the form of a white powder;
[0075] Into a 250mL three-necked flask equipped with a mechanical stirring device and a condenser, 4g of the first intermediate product (0.018mol), 3g of the second intermediate product (0.018mol) and 40mL of anhydrous ethanol were added. After nitrogen was introduced into the three-necked flask to expel oxygen, 0.28g of acetic acid was added dropwise. The mixture was reacted for 1h under a nitrogen atmosphere at 50°C, and then cooled to room temperature. The solid was filtered and washed with anhydrous ethanol. The solid was then placed in a vacuum oven and dried in vacuo at 25°C for 24h to obtain a white powder product.
[0076] Example 3
[0077] This embodiment provides a method for preparing a photocurable mussel biomimetic acylhydrazone, comprising the following steps:
[0078] 30 g of vanillin (0.20 mol), 34 g of methacrylic anhydride (0.22 mol) and 0.2 g of 4-dimethylaminopyridine were added to a 250 mL three-necked flask equipped with a mechanical stirring device and a condenser. After nitrogen was introduced into the three-necked flask to expel oxygen, the mixture was stirred for 24 h under a nitrogen atmosphere and a temperature of 60 ° C., and then cooled to room temperature. After adding 150 mL of dichloromethane, the mixture was transferred to a separatory funnel, first washed with 150 mL of saturated NaHCO3 solution until no bubbles were generated in the mixture, and then washed with 150 mL of 0.5 mol / L NaOH solution and 150 mL of 1 mol / L NaOH solution for 3 times, respectively, and finally washed with deionized water for 3 times, the organic phase was collected and dried overnight with anhydrous magnesium sulfate, the organic phase was concentrated with a rotary evaporator, and the concentrated organic phase was transferred to a glass culture dish, and the glass culture dish was placed in a vacuum oven at 25 ° C. and vacuum dried for 24 h to obtain a first intermediate product as a white solid;
[0079] 8 g of methyl 3,4-dihydroxybenzoate (0.048 mol) and 30 mL of anhydrous ethanol were added to a 250 mL three-necked flask equipped with a mechanical stirring device and a condenser, and the mixture was stirred for 15 minutes until methyl 3,4-dihydroxybenzoate was dissolved in the anhydrous ethanol. Nitrogen was introduced into the three-necked flask to expel oxygen, and then 6 g of a hydrazine hydrate solution (0.096 mol) with a mass fraction of 80% was added. The temperature was raised to 30° C. and reacted for 24 h, then cooled to room temperature and filtered, and the solid was washed with anhydrous ethanol until it was neutral, and then the solid was placed in a vacuum oven and vacuum dried at 25° C. for 24 h to obtain a second intermediate product in the form of a white powder;
[0080] Into a 250mL three-necked flask equipped with a mechanical stirring device and a condenser, 4g of the first intermediate product (0.018mol), 3g of the second intermediate product (0.018mol) and 40mL of anhydrous ethanol were added. After nitrogen was introduced into the three-necked flask to expel oxygen, 0.1750g of acetic acid was added dropwise. The mixture was reacted for 1h under a nitrogen atmosphere at 50°C, and then cooled to room temperature. The solid was filtered and washed with anhydrous ethanol. The solid was then placed in a vacuum oven and dried in vacuo at 25°C for 24h to obtain a white powder product.
[0081] Vanillin (VA), methyl 3,4-dihydroxybenzoate (MD), the first intermediate product vanillin methyl methacrylate (VA-MA), the second intermediate product protocatechuic acid benzohydrazide (MD-HH) and the product photocured mussel biomimetic acylhydrazone (MH-VM) in Examples 1-3 were measured respectively to illustrate the successful synthesis of vanillin methyl methacrylate, methacrylic anhydride and photocured mussel biomimetic acylhydrazone.
[0082] The following is a detailed description using Example 3 as an example, and the VA, MD, VA-MA, MD-HH and MH-VM of Example 3 are measured respectively to illustrate the successful synthesis of the product, the photocured mussel biomimetic acylhydrazone.
[0083] Infrared spectroscopic tests were performed on VA and VA-MA, and the results were as follows: Figure 2 As shown. Figure 2 It can be seen that 3360cm -1 The absorption peaks around 2849cm are attributed to the stretching vibration peak of the phenolic hydroxyl group of vanillin, but the absorption peaks disappear in VA-MA, indicating that vanillin has completely reacted with methacrylic anhydride. -1 The absorption peak at 1741 cm is attributed to the CH stretching vibration of the aldehyde group. -1 、1703cm -1 and 1637cm -1 The absorption peaks are attributed to -OC=O, HC=O and C=C, respectively, which also confirms that methacrylic anhydride and vanillin have successfully undergone Steglich esterification reaction, indicating the successful synthesis of vanillin methyl methacrylate.
[0084] VA was analyzed by 1H NMR with (CD3)2CO as solvent, and VA-MA was analyzed by 1H NMR with CDCl3 as solvent. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the peak at 9.9ppm belongs to the proton peak on the aldehyde group of vanillin methyl methacrylate, which indicates that the aldehyde group is well retained. The proton peak on the benzene ring appears between 7.5ppm and 7.2ppm, and the proton peaks of the double bond are located at 6.3ppm and 5.7ppm respectively. Since the methyl group is in different environments, the peaks appear at 3.8ppm and 2.0ppm respectively, of which the peak at 2.0ppm belongs to the proton peak on the methyl group on methacrylic anhydride. The above results indicate the successful synthesis of vanillin methyl methacrylate.
[0085] The infrared spectra of MD and MD-HH were tested. Figure 4 As shown. Figure 4 It can be seen that 1688cm -1 The absorption peak at 1660 cm-1 is attributed to the stretching vibration of the carbonyl group (C=O) of 3,4-dihydroxybenzoic acid methyl ester. After reacting with hydrazine hydrate, the absorption peak disappears and the peak at 1660 cm-1 is -1 A new absorption peak appeared, which was attributed to the stretching vibration of C=O of hydrazide. -1 A new absorption peak appeared, which was attributed to the bending vibration of hydrazide NN, 3362 cm -1 and 3193cm -1The absorption peak is attributed to the stretching vibration of NH. The above results indicate the successful synthesis of protocatechuic acid benzoyl hydrazide.
[0086] 1H NMR analysis of MD was performed using (CD3)2CO as solvent, and 1H NMR analysis of MD-HH was performed using (CD3)2SO as solvent. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that the peaks between 7.5ppm and 6.9ppm belong to the proton peaks on the benzene ring, the peak at 3.8ppm belongs to the proton peak of -CH3 connected to the ester oxygen of MD, and in the H NMR spectrum of MD, the peaks at 8.3ppm and 8.6ppm belong to the two phenolic hydroxyl groups. In the H NMR spectrum of protocatechuic acid benzoyl hydrazide, the peaks at 9.2-9.4ppm belong to the two phenolic hydroxyl groups. Compared with MD, the proton peak of -CH3 connected to the ester oxygen at 3.8ppm in MD-HH disappears, and the proton peak of -NH2 belonging to hydrazide appears at 4.3ppm. The above results indicate the successful synthesis of protocatechuic acid benzoyl hydrazide.
[0087] The infrared spectrum of MH-VM was tested and compared with the infrared spectrum of VA-MA and MD-HH. Figure 6 As shown. Figure 6 It can be seen that compared with the infrared spectrum detection results of VA-MA and MD-HH, the infrared spectrum of MH-VM at 1703 cm -1 The C=O absorption peak of the aldehyde group disappears. At the same time, the absorption peak at 1639 cm -1 A new characteristic absorption peak appears at , which is attributed to the stretching vibration of C=N of acylhydrazone, overlapping with the stretching vibration of C=C, indicating that the aldehyde group of VA-MA and the hydrazide of MD-HH react to form an acylhydrazone group (O=C-NH-N=C). The above results indicate the successful synthesis of photocured mussel biomimetic acylhydrazone.
[0088] 1H NMR analysis of MH-VM was performed using (CD3)2SO as solvent. The results are as follows: Figure 7 As shown. Compared with the H NMR spectra of VA-MA and MD-HH, the peak at 9.9ppm in the H NMR spectrum of MH-VM, which belongs to the proton peak on the aldehyde group, and the proton peak -NH2 at 4.3ppm, which belongs to the hydrazide, disappeared, indicating that the reaction of VA-MA and MD-HH consumed the aldehyde group of VA-MA and the hydrazide of MD-HH, and a new proton peak -CH=N belonging to the acylhydrazone group appeared at 8.4ppm. At the same time, the product was relatively pure, and there was no unreacted VA-MA and MD-HH residue. The above results indicate the successful synthesis of the photocurable mussel biomimetic acylhydrazone.
[0089] Infrared spectroscopy and 1H NMR analysis were performed on VA, MD, VA-MA, MD-HH and MH-VM in Examples 1-2, respectively. The characteristic peaks of the infrared spectroscopy results and the proton peaks of the 1H NMR results were consistent with those in Example 3, indicating that VA-MA, MD-HH and MH-VM in Experimental Examples 1-2 were also successfully synthesized.
[0090] Example 4
[0091] This embodiment provides a mussel biomimetic light-curing adhesive composition.
[0092] 0.5 g of the photocurable mussel biomimetic acylhydrazone prepared in Example 1 was dissolved in 0.75 g of dimethyl sulfoxide, 3.5 g of polyethylene glycol dimethacrylate (number average molecular weight of 800) and 0.25 g of PI-1173 were added, and mixed evenly to obtain a mussel biomimetic photocurable adhesive composition, which was recorded as F1.
[0093] Example 5
[0094] This embodiment provides a mussel biomimetic light-curing adhesive composition.
[0095] 1 g of the photocurable mussel biomimetic acylhydrazone prepared in Example 2 was dissolved in 0.75 g of dimethyl sulfoxide, 3 g of polyethylene glycol dimethacrylate (number average molecular weight of 800) and 0.25 g of PI-1173 were added, and mixed evenly to obtain a mussel biomimetic photocurable adhesive composition, which was recorded as F2.
[0096] Example 6
[0097] 1.5 g of the photocurable mussel biomimetic acylhydrazone prepared in Example 3 was dissolved in 0.75 g of dimethyl sulfoxide, and 2.5 g of polyethylene glycol dimethacrylate (number average molecular weight of 800) and 0.25 g of PI-1173 were added and mixed evenly to obtain a mussel biomimetic photocurable adhesive composition, which was recorded as F3.
[0098] Comparative Example 1
[0099] This comparative example provides a photocurable adhesive composition.
[0100] 4 g of polyethylene glycol dimethacrylate (number average molecular weight of 800), 0.75 g of dimethyl sulfoxide and 0.25 g of PI-1173 were mixed uniformly to obtain a photocurable adhesive composition, which was recorded as F0.
[0101] Experimental Example 1
[0102] In this experimental example, the mussel biomimetic photocurable adhesive compositions of Examples 4-6 and the photocurable adhesive composition of Comparative Example 1 were subjected to differential scanning calorimetry analysis. The test results are as follows: Figure 8 As shown. Figure 8 It can be seen that with the increase of the content of photocurable mussel bionic acylhydrazone in the photocurable adhesive composition, the heat flow of the mussel bionic photocurable adhesive composition within a certain temperature range changes little, and the glass transition temperature increases, indicating that photocurable mussel bionic acylhydrazone is beneficial to the enhancement of thermal stability.
[0103] Experimental Example 2
[0104] In this experimental example, the overlapping method was used to test the bonding performance of the mussel biomimetic photocurable adhesive composition of Examples 4-6 and the photocurable adhesive composition (F0-F3) of Comparative Example 1.
[0105] The lap shear test was evaluated using a SUNS Technology UTM 6104 universal tensile machine. The substrates included acrylic (PMMA), aluminum sheets (AL) and planks (Plank). Before use, the substrates were cleaned and ultrasonicated in ethanol for 30 minutes, then air-dried overnight. 0.30 g of F0-F3 was applied to the acrylic respectively, and then the substrates were placed on the acrylic to form a square lap area of 2 cm × 2 cm. Finally, the samples were cured by UV curing machine. After F0-F3 was cured by UV light at a wavelength of 365 nm for 120 seconds, the lap shear test was immediately carried out. The sample preparation method is as follows: Fig. 9 Then, the F0-F3 bonded specimens were placed on a vertical fixture, and the crosshead of the universal tensile machine was uniformly loaded at a strain rate of 5 mm / min to test the stress that causes the bonded joint to fail under the tensile load parallel to the axial direction of the bonded surface layer. Each specimen was tested 3 to 5 times to obtain the average value and standard mean error. The results are shown in Fig.10 shown.
[0106] from Fig.10 It can be seen that with acrylic, aluminum sheet and wood as substrates, the bonding strength of F1-F3 is improved compared with F0, and with the increase of the content of light-cured mussel bionic acylhydrazone, the bonding strength also increases, indicating that light-cured mussel bionic acylhydrazone can enhance the adhesion performance of mussel bionic photocurable adhesive composition on different substrates. Among them, the adhesion performance of mussel bionic photocurable adhesive to aluminum sheet as substrate is significantly improved. It can be observed that F0 without light-cured mussel bionic acylhydrazone can hardly form effective adhesion with aluminum sheet, and the maximum bonding strength of the specimen bonded with aluminum sheet by mussel bionic photocurable adhesive is increased to 0.5973MPa.
[0107] Experimental Example 3
[0108] In this experimental example, the mussel biomimetic photocurable adhesive composition of Examples 4-6 and the photocurable adhesive composition (F0-F3) of Comparative Example 1 were subjected to thermogravimetric analysis test.
[0109] 3 to 5 g of F0-F3 were respectively placed in a culture dish with a diameter of 100 mm, left to stand for half an hour, and then exposed to 365 nm ultraviolet light for 120 seconds to obtain the cured films of F0-F3 of this experimental example.
[0110] The test results are as follows Fig.11 As shown, Fig.11 (a) is the TGA curve of the cured films of F0-F3, Fig.11 (b) is the DTG curve of the cured film of F0-F3. Fig.11 It can be seen that the maximum thermal degradation temperature of the cured films of F1-F3 is about 400°C, which is slightly higher than the maximum thermal degradation temperature of the cured film of F0. 10% ), 50% thermal degradation temperature (T 50% ) and the maximum degradation rate temperature (T max ) and the residual carbon rate at 700℃ are listed in Table 1. As can be seen from Table 1, with the increase of the content of light-cured mussel biomimetic acylhydrazone, T max The value increases first and then decreases, T max The highest temperature can reach 402℃, T 50% The highest temperature can reach 393.1℃. Compared with the cured film of F0, with the increase of the content of light-cured mussel biomimetic acylhydrazone, the carbon residue of the cured film first decreases and then increases. The above results show that the mussel biomimetic light-cured adhesive composition has good thermal stability.
[0111] Table 1 Thermal decomposition data of F0-F3 cured films
[0112] sample <![CDATA[T 10% (℃)]]> <![CDATA[T 50% (℃)]]> <![CDATA[T max (1 st / 2 nd / 3 rd )(℃)]]> Carbon residue rate (%) F0 322.9 383.4 40.2 / 390.3 8.21 F1 309.5 389.5 41.3 / 91.4 / 400.9 0.52 F2 249.6 393.1 41.2 / 101.4 / 402.0 11.92 F3 118.4 387.4 43.9 / 108.6 / 397.9 13.36
[0113] Experimental Example 4
[0114] In this experimental example, the infrared absorption peak area of the main functional groups of the mussel biomimetic photocurable adhesive composition of Examples 4-6 and the photocurable adhesive composition (F0-F3) of Comparative Example 1 before and after photocuring was tested. 3-5g of F0-F3 were placed in a culture dish with a diameter of 100mm, left to stand for half an hour, and then placed under 365nm ultraviolet light for 120 seconds to obtain the cured films of F0-F3 for subsequent testing. The test results are as follows: Fig.12 As shown, Fig.12 (a) is the infrared absorption peak of the main functional groups of F0-F3 before photocuring, Fig.12 (b) is the infrared absorption peak of the main functional groups of F0-F3 after photocuring. Fig.12It can be seen that after adding the photocurable mussel biomimetic acylhydrazone, the conversion rate of C=C has a significant decrease, which may be caused by the inhibition effect of phenolic hydroxyl groups. However, the lowest conversion rate of C=C after photocuring can also be greater than 60%, indicating that the carbon-carbon double bond conversion rate of the mussel biomimetic photocurable adhesive composition after UV curing is still at a good level.
[0115] Experimental Example 5
[0116] In this experimental example, general performance analysis was performed on the cured films of the mussel bionic photocurable adhesive compositions of Examples 4-6 and the photocurable adhesive composition (F0-F3) of Comparative Example 1, and acid resistance, alkali resistance, gel fraction and pencil hardness were tested respectively. The test results are listed in Table 2.
[0117] The preparation method of the F0-F3 cured film of this experimental example is to put 3-5g of F0-F3 into a culture dish with a diameter of 100mm and let it stand for half an hour, and then put it under 365nm ultraviolet light for 120 seconds to obtain the obtained film.
[0118] The acid resistance test method is to weigh 0.2000-0.5000g of the cured films of samples F0-F3 respectively at room temperature, immerse them in a sealed glass bottle filled with 10% hydrochloric acid solution for 24 hours, and record the morphology of the samples before and after immersion.
[0119] The alkali resistance test method is to weigh 0.2000-0.5000g of the cured films of samples F0-F3 respectively at room temperature, immerse them in a sealed glass bottle filled with 10% sodium hydroxide solution for 24 hours, and record the morphology of the samples before and after immersion.
[0120] The gel content test method is to weigh 0.2000-0.5000g of the cured film of samples F0-F3 at room temperature and immerse them in a sealed glass bottle filled with acetone. After immersion for 48 hours, take out the cured film sample and place it in a 60°C vacuum drying oven to dry to constant weight. Record the mass W0 of the cured film before immersion and the mass W1 of the cured film after drying. The gel content is obtained by calculation. Each sample is measured three times and the average value is taken. The calculation formula is:
[0121]
[0122] The pencil hardness test method is to test the pencil hardness of the cured films of samples F0-F3 according to GB / T 6739-1996 standard.
[0123] Table 2 General performance analysis of cured films of F0-F3
[0124] sample Acid resistance Alkali resistance Gel rate (%) Pencil hardness F0 No significant changes No significant changes 89.22±0.71 5B F1 No significant changes Surface turns brown 73.88±0.22 1H F2 No significant changes Surface turns brown 70.96±0.60 1H F3 No significant changes Surface turns brown 66.99±0.68 2H
[0125] It can be seen from Table 2 that compared with the photocurable adhesive composition, the cured film of the mussel biomimetic photocurable adhesive composition with the addition of photocurable mussel biomimetic acylhydrazone has good acid resistance, but the alkali resistance and gel rate decrease, and the pencil hardness test result improves. With the increase of the content of photocurable mussel biomimetic acylhydrazone, the gel rate of the cured film decreases, which may be due to the inhibition of phenolic hydroxyl groups affecting the crosslinking degree of the cured film. The pencil hardness test result is good, indicating that the photocurable mussel biomimetic acylhydrazone can increase the wear resistance of the cured film of the photocurable adhesive composition.
[0126] Therefore, compared with the prior art, the beneficial effects of the present invention are:
[0127] (1) The photocurable mussel biomimetic acylhydrazone of the present invention has low raw material cost; its molecular structure has both a catechol structure that simulates mussel adhesion and a carbon-carbon double bond that can participate in photocuring, and can be used as a new type of mussel biomimetic material;
[0128] (2) The preparation method of the light-cured mussel biomimetic acylhydrazone of the present invention comprises the following steps: firstly, methacrylic anhydride and vanillin undergo a Steglich esterification reaction to synthesize vanillin methyl methacrylate, then 3,4-dihydroxybenzoic acid methyl ester and hydrazine hydrate undergo an ester hydrazinolysis reaction to synthesize protocatechuic acid benzoyl hydrazide, and finally, vanillin methyl methacrylate and protocatechuic acid benzoyl hydrazide undergo a Schiff base reaction to synthesize the light-cured mussel biomimetic acylhydrazone. The synthesis process does not require the protection and deprotection of the catechol structure, the preparation method is simple, and the synthesis difficulty and production cost of the mussel biomimetic material are reduced;
[0129] (3) The mussel biomimetic photocurable adhesive composition prepared by the present invention using photocurable mussel biomimetic acylhydrazone as raw material, the carbon-carbon double bonds of the photocurable mussel biomimetic acylhydrazone undergo cross-linking reaction with the resin matrix, and the catechol structure is used to give the composition good adhesive properties. At the same time, within the preferred addition amount range, the carbon-carbon double bond conversion rate after photocuring is high, and the curing effect and mechanical properties of the adhesive are good. The problem of insufficient adhesion and failure of the photocurable adhesive causing shedding can be improved. In addition, the cured film of the mussel biomimetic photocurable adhesive composition of the present invention has good acid resistance and coating hardness.
[0130] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A photocurable mussel biomimetic acylhydrazone, characterized in that: The structural formula of the photocurable mussel biomimetic acylhydrazone is shown in formula (I):
2. The method for preparing the light-cured mussel biomimetic acylhydrazone according to claim 1, characterized in that: The following steps are involved: Dissolve vanillin methyl methacrylate and protocatechuic acid benzoyl hydrazide in an organic solvent, add acetic acid in a nitrogen atmosphere, react at 50-80°C for 1-4h, then purify and dry to obtain; The molar ratio of the vanillin methyl methacrylate to the protocatechuic benzoyl hydrazide is 1:(0.9-1.3), and the organic solvent is selected from at least one of methanol and anhydrous ethanol.
3. The preparation method according to claim 2, characterized in that: The amount of acetic acid used is 2-5% of the total mass of vanillin methyl methacrylate, protocatechuic acid benzoyl hydrazide and acetic acid.
4. The preparation method according to claim 2, characterized in that: The preparation method of vanillin methyl methacrylate comprises the following steps: Mix vanillin, methacrylic anhydride and 4-dimethylaminopyridine, react at 50-80°C for 24-48h in a nitrogen atmosphere, and then purify and dry to obtain; Wherein, the molar ratio of the vanillin to the methacrylic anhydride is 1:(1.1-2.0).
5. The preparation method according to claim 4, characterized in that: The amount of 4-dimethylaminopyridine used is 0.2-1% of the total mass of vanillin, methacrylic anhydride and 4-dimethylaminopyridine.
6. The preparation method according to claim 2, characterized in that: The preparation method of vanillin methyl methacrylate comprises the following steps: Dissolve methyl 3,4-dihydroxybenzoate in an organic solvent, add hydrazine hydrate solution in a nitrogen atmosphere, react at 25-80°C for 2-24h, then purify and dry to obtain; Wherein, the molar ratio of the methyl 3,4-dihydroxybenzoate to the hydrazine hydrate is 1:(1.0-2).
7. The preparation method according to claim 6, characterized in that: The mass fraction of hydrazine hydrate in the hydrazine hydrate solution is 70-90%, and the organic solvent is selected from at least one of methanol and anhydrous ethanol.
8. Use of the photocurable mussel biomimetic acylhydrazone according to claim 1 in a mussel biomimetic photocurable adhesive composition.
9. A mussel biomimetic light-curing adhesive composition, characterized in that: It is prepared from a reaction system of a resin matrix, a solvent, a photoinitiator and the photocurable mussel biomimetic acylhydrazone according to claim 1; The mass of the resin matrix is 50% to 80% of the total mass of the reaction system, the mass of the solvent is 10% to 20% of the total mass of the reaction system, the mass of the photoinitiator is 4% to 6% of the total mass of the reaction system, and the mass of the photocurable mussel biomimetic acylhydrazone is 1% to 30% of the total mass of the reaction system; The resin matrix is polyethylene glycol dimethacrylate; the solvent is selected from at least one of dimethyl sulfoxide, tetrahydrofuran, and N,N-dimethylformamide; and the photoinitiator is selected from at least one of PI-1173, PI-2959, and TPO.
10. The method for preparing the mussel biomimetic light-curing adhesive composition according to claim 9, characterized in that: The photocurable mussel biomimetic acylhydrazone is dissolved in a solvent, and then a resin matrix and a photoinitiator are added and mixed evenly to obtain the product.
Citation Information
Patent Citations
Benzoylhydrazone compound, and preparation method and application thereof
CN111848440A
Acylhydrazone structure-based ultraviolet light-cured polyurethane precursor, preparation method and application thereof
CN112390928A
High bio-based UV (ultraviolet) resin containing imine bonds as well as preparation method and application of high bio-based UV resin
CN117603418A